Étude numérique de la stabilité des ouvrages de soutènement - عثمان, بن كادي; عادل عبد الحكيم, مشانة; مروة, مليك; لمياء, بده (University of El-Oued, 2022)
"Urban excavations require the use of retroactive structures to protect existing adjacent buildings. These structures are often used in civil engineering ; Calculation and determination of the dimensions of these structures are not easy, interactions between soil, wall and adjacent structures are important, and therefore taking them into account is difficult. The objectif of this work relates to numerical modeling and the analysis of the stability of a barrier-type wall of pigments completed with reinforced concrete installed in sand soil using the limited element method using two programs: Plaxis 2D- v8.5 and Plaxis 3D- v2013. The analysis applies to a real situation, and it concerns a wall formed from a barrier of pilgrims to support drilling during the completion of an underpass at the crossroads of TIKSEBET, at the north of Eloued city (Algeria). The impact of the soil behaviour model, water level rise and peg length on horizontal deformation, safety coefficients, and comparison of 2D and 3D modelling results highlighted in this numerical study." "تتطلب الحفريات في المناطق الحضرية استخدام الهياكل الاستنادية لحماية المباني المجاورة. غالبا ما تستخدم هذه الهياكل في مجال الهندسة المدنية ؛ إلا أن الحساب و تحديد أبعاد هذه الهياكل ليسا بسيطين ؛ حيث تعتبر التفاعلات بين التربة و الجدار و الهياكل المجاورة مهمة، و بالتالي يكون أخذها في الاعتبار أمرًا صعبًا. يتعلق الهدف من هذا العمل بالنمذجة الرقمية و تحليل ثبات جدار مشكل من حاجز من الخوازيق المنجزة بالخرسانة المسلحة مثبتة في تربة رملية باستعمال طريقة العناصرالمحدودة باستخدام برنامجين: البلاكسيس ثنائي الأبعاد (Plaxis 2D- v8.5) والبلاكسيس ثلاثي الأبعاد(Plaxis 3D- v2013). ينطبق التحليل على حالة حقيقية، و يتعلق الأمر بجدار مشكل من حاجز من الخوازيق لدعم الحفر أثناء إنجاز ممر سفلي على مفترق طرق تكسبت، بالمدخل الشمالي لمدينة الوادي (الجزائر(. إن تأثير نموذج سلوك التربة، ارتفاع منسوب المياه و طول الوتد، على التشوه الأفقي، معامل الأمان و المقارنة بين نتائج النمذجة ثنائية الأبعاد (2D) و ثلاثية الأبعاد (3D) تم أخذها بعين الاعتبار في هذه الدراسة العددية."
مذكرات ماستر تخصص هندسة مدنية
Keywords: retaining, numerical modeling, excavation, stability, pile, behavior.; الإسناد، النمذجة الرقمية، الحفر، الاستقرار، الخازوق، السلوك.